2015
DOI: 10.2166/wst.2015.293
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbons from waste of oil-palm kernel shells, sawdust and tannery leather scraps and application to chromium(VI), phenol, and methylene blue dye adsorption

Abstract: Phenol, chromium, and dyes are continuously dumped into water bodies; the adsorption of these contaminants on activated carbon is a low-cost alternative for water remediation. We synthesized activated carbons from industrial waste of palm oil seed husks (kernel shells), sawdust, and tannery leather scraps. These materials were heated for 24 h at 600, 700 or 800°C, activated at 900°C with CO2 and characterized by proximate analysis and measurement of specific surface area (Brunauer-Emmett-Teller (BET) and Langm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The UV spectrophotometer was calibrated against a standard solution before each set of measurements. The adsorption ( R %) and amounts of naphthalene adsorbed at equilibrium ( q e ) and any time ( q t ) on the starch‐modified Fe 0 nanoparticle adsorbent were determined according to equations (1)–(3), respectively: R%=C0CtC0×100 qe=()C0CeVW qt=()C0CtVW where C 0 , C e and C t are the initial, equilibrium and any time ( t ) concentration of naphthalene (mg l −1 ), respectively, W is the mass of starch‐modified Fe 0 nanoparticle adsorbent (g) and V is the volume of naphthalene solution (l).…”
Section: Methodsmentioning
confidence: 99%
“…The UV spectrophotometer was calibrated against a standard solution before each set of measurements. The adsorption ( R %) and amounts of naphthalene adsorbed at equilibrium ( q e ) and any time ( q t ) on the starch‐modified Fe 0 nanoparticle adsorbent were determined according to equations (1)–(3), respectively: R%=C0CtC0×100 qe=()C0CeVW qt=()C0CtVW where C 0 , C e and C t are the initial, equilibrium and any time ( t ) concentration of naphthalene (mg l −1 ), respectively, W is the mass of starch‐modified Fe 0 nanoparticle adsorbent (g) and V is the volume of naphthalene solution (l).…”
Section: Methodsmentioning
confidence: 99%
“…The point of zero charge of activated carbon produced from leather waste in Palani et al [27] study was 7.6, thus confirming the interaction of the surface of the positively charged material with chromium (VI) in its anionic form. In the study by Montoya-Suarez et al [43] the experiments were conducted at pH 7.0, a factor that caused the lowest Chromium (VI) adsorption capacity (0.10 mg/g) compared to the other studies.…”
Section: Adsorptionmentioning
confidence: 99%
“…They also applied the same procedure to prepare adsorbent from oil palm trunks without treatment and found high malachite green uptake of 149.35 mg/g [25]. Meanwhile, Montoya-Suarez et al [26] studied the physical treatment of oil palm shell at 600-800°C and obtained adsorbent with high surface area of 1268 m 2 /g.…”
Section: Removal Of Dyes Using Oil Palm Adsorbentsmentioning
confidence: 99%
“…The removal uptake for copper, lead and mercury were at a high of 52.5 mg/g. Meanwhile, Montoya-Suarez et al [26] found that adsorbent obtained from pyrolysis of oil palm shell at 600-800 C was able to remove only 0.37 mg/g of chromium ions. Similar findings were reported by Rehman et al [48] who studied oil palm clinker sand as adsorbents and obtained an arsenic uptake of 9 mg/g.…”
Section: Removal Of Pesticides Using Oil Palm Adsorbentsmentioning
confidence: 99%